Pengaruh Fisioterapi Terhadap Parameter Hemodinamik pada Pasien Kritis Di ICU RSUP Dr. Sardjito - Hanafi, Irham; Sari, Djayanti; Jufan, Akhmad Yun (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Background: Critically ill patients undergoing treatment in the ICU experience long-term immobilization. Giving physiotherapy to patients is a recommendation to mobilize critically ill patients early to prevent complications. Monitoring vital signs is important to ensure that physiotherapy is safe and that the patient is protected from the adverse effects of physiotherapy. The recording of hemodynamic changes has never been done in Dr. Sardjito General Hospital. Objective: To determine the effect of passive motion physiotherapy on hemodynamic parameters in critically ill patients admitted to the ICU. Method: This study used a quasi-experimental interventional design. Patients who entered the inclusion criteria were patients who were treated in the ICU and aged over 18 years in June and July 2021. Hemodynamic data were taken from bedside monitors and ICON devices. Results: The number of research subjects was 32 patients. Passive motion physiotherapy resulted in a lower SVV value (10.84 ± 6.19; p = 0.014) than at baseline (12.91 ± 6.19) and after rest (12.25 ± 5.21). Other parameters, HR, RR, SBP, DBP, MAP, SV, SI, CO, CI, SVR, and DO2 did not produce statistically significant changes. Conclusion: Passive motion physiotherapy has no effect on hemodynamic parameters in critically ill patients admitted to the ICU Dr. Sardjito General Hospital. Passive motion physiotherapy resulted in lower SVV compared to baseline and resting conditions.